JUNIOR HIGH SCHOOL STUDENTS’ LEARNING STYLES IN LEARNING ENGLISH - Hustarna; Masbirorotni (JELT (Jambi-English Language Teaching), 2024)
The success of English teaching and learning process depends on many things. One of them is the compatibility of the teaching method, teaching and learning process, and the characteristics of the students. One of the students’ characteristics is learning styles when learning English. This study aims at investigating learning styles of students at two state junior high schools in Jambi city. This study employed descriptive and quantitative research design, using a questionnaire as the instrument. The result of the study shows that of the sixth learning styles, the learning styles mostly used by the students are kinesthetic, tactile, and learning in group. Besides, the students appear to exhibit multiple minor learning styles.